(untitled) (Bangladesh Agronomy Journal, 2017)
In lowland rice production systems, flooding patterns vary during the cropping period and this poses a serious challenge to productivity due to the effect of flooding on the availability and uptake of nitrogen. The aim of this study was to examine the influence of various flooding patterns on nitrogen use in rice grown under simulated wetland conditions. Rice was grown in a greenhouse at 0, 110 and 220 kg N ha-1 under well watered control conditions, continuous flooding, early flooding at tillering, and late flooding post-tillering. The results showed that continuous and early flooding increased tiller production and grain yield compared to late flooding or non-flooded conditions. Although the highest grain yields under the different flooding patterns were obtained with 220 kg N ha-1, the combination of 110 kg N ha-1 and early flooding also significantly increased tiller productivity, nitrogen recovery, and agronomic nitrogen use efficiency (NUE). There is the need to regulate the supply of nitrogen and water resources if grain yield and NUE has to be increased at minimal costs. Also, compared to well-watered conditions, rice production under flooded conditions lead to increased productivity and N rate must match realistic target yields. Best results are obtained when flooding occurs in the early rather than later parts of the season. Bangladesh Agron. J. 2017, 20(1): 67-75